Interaction of isoniazid with Mycobacterium tuberculosis enoyl-acyl carrier protein reductase (InhA): from bioinformatics perspective. - Choong, Yee Siew; Wahab, Habibah A; Ibrahim, Pazilah; Sadikun, Amirin (Penerbit Universiti Sains Malaysia, 2004)
Tuberculosis (TB), caused by Mycobacterium tuberculosis is a leading killer that has plagued mankind for centuries. The disease is estimated to infect 8 million and kill 2 - 3 million people each year (Rouse et al., 1995; Manca et al., 1997). A frequently used drug to treat TB is isonicotinic acid hydrazide (INH/ isoniazid) but unfortunately, INHresistant M. tuberculosis organisms are becoming quite common now.